ANALISIS STRATEGI PENGEMBANGAN USAHA KERUPUK LENTO I & G BERSAUDARA TANJUNG ANAU KELURAHAN OMPANG TANAH SIRAH KECAMATAN PAYAKUMBUH UTARA - Ilfa Hanim; Muhammad Rais (Adisam Publisher, 2026)
The objective of this research is to examine the business development tactics of Kerupuk Lento I & G Bersaudara situated in Balai Batung Village, North Payakumbuh District. The investigative method utilizes a qualitative perspective with SWOT analysis through the formulation of Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Information was gathered via interviews and field observations, and documentation. The results indicate that Kerupuk Lento I & G Bersaudara is strategically positioned aggressively, characterized by strong internal factors and substantial external opportunities. Recommended strategies include increasing production efficiency, strengthening promotion through digital media and packaging innovation, and expanding the distribution network or opening branches. Implementing these strategies is expected to increase competitiveness and business sustainability in accordance with Sharia principles.